Respiratory viral infections within one year after pediatric lung transplant - Liu, M.; Worley, S.; Arrigain, S.; Aurora, P.; Ballmann, M.; Boyer, D.; Conrad, C.; Eichler, I.; Elidemir, O.; Goldfarb, S.; Mallory, G.B.; Mogayzel, P.J.; et al. (Transplant infectious disease, 2009)
: To characterize epidemiology and risk factors for respiratory viral infections (RVI) in pediatric lung transplant recipients within the first post‐transplant year, a retrospective multicenter study of pediatric lung transplant recipients from 1988 to 2005 was conducted at 14 centers in the United States and Europe. Data were recorded for 1 year post transplant. Associations between RVI and continuous and categorical risk factors were assessed using Wilcoxon's rank‐sum and χ2 tests, respectively. Associations between time to RVI and risk factors or survival were assessed by multivariable Cox proportional hazards models. Of 576 subjects, 79 subjects (14%) had 101 RVI in the first year post transplant. Subjects with RVI were younger than those without RVI (median ages 9.7, 13; P<0.01). Viruses detected included adenovirus (n=25), influenza (n=9), respiratory syncytial virus (n=21), parainfluenza virus (n=19), enterovirus (n=4), and rhinovirus (n=22). In a multivariable model for time to first RVI, etiology other than cystic fibrosis (CF), younger age, and no induction therapy were independently associated with risk of RVI. Cytomegalovirus serostatus and acute rejection were not associated with RVI. RVI was independently associated with decreased 12‐month survival (hazard ratio 2.6, 95% confidence interval 1.6–4.4). RVI commonly occurs after pediatric lung transplantation with risk factors including younger age and non‐CF diagnosis. RVI is associated with decreased 1‐year survival.